Modulation of CYP1A1-mediated oxidation of carcinogenic azo dye Sudan I and its binding to DNA by cytochrome b5 - Stiborová, Marie; Martínek, Vaclav; Schmeiser, Heinz H; Frei, Eva (Neuro endocrinology letters, 2006)
OBJECTIVES: Modulation of the cytochrome P450 (CYP) 1A1-mediated oxidative activation and detoxication of carcinogenic Sudan I by the heme-protein cytochrome b(5) (b(5)) was investigated. Another aim of the study was to examine the formation of Sudan I-DNA adducts in vivo. METHODS: High performance liquid chromatography (HPLC) with ultraviolet (UV) detection was employed for the separation of Sudan I metabolites formed by human recombinant CYPs and rat CYP1A1. The (32)P-postlabeling technique was utilized to determine Sudan I-DNA adducts. RESULTS: The capabilities of the most efficient CYP enzymes oxidizing Sudan I, human and rat recombinant CYP1A1, as well as of human recombinant CYP1A2, 2A6 and 3A4 were significantly increased by b(5), while reactions catalyzed by human CYP1B1, 2C8, 2C9 and 2E1 were insensitive to this heme protein. Sudan I oxidation catalyzed by CYP2B6, 2C19 and 2D6 was even decreased by b(5). The stimulation of the CYP1A1-mediated Sudan I oxidation was dependent on concentration of b(5). Likewise, the increase in CYP1A1-mediated formation of Sudan I-DNA adducts by b(5) was concentration dependent. Other proteins containing heme such as cytochrome c or myoglobin were without this effect. The major Sudan I-DNA adducts formed in vitro are also generated in vivo, in livers of rats treated with Sudan I. CONCLUSIONS: The data are the first report on the stimulation of CYP1A1-mediated oxidative reactions by b(5). In addition, the results demonstrating covalent binding of Sudan I to rat liver DNA in vivo indicate a genotoxic mechanism of Sudan I carcinogenicity in rats.
Keywords: Coloring Agents; adukty DNA; Male; Rats, Wistar; Cytochrome P-450 CYP1A1; naftoly; cytochrom P-450 CYP1A1; mužské pohlaví; Naphthols; potkani Wistar; Metabolic Detoxication, Phase I; Models, Biological; králíci; krysa rodu Rattus; Animals; lidé; biologické modely; barvicí látky; Humans; DNA Adducts; zvířata; I. fáze biotransformace; Rats; Rabbits; DNA; cytochromy b5; Cytochromes b5